The Role and Scope of Intuition (Anschauung) in Kant Transcendental Philosophy - Krioukov, Alexei (Con-Textos Kantianos. International Journal of Philosophy, 2025)
Kant's notion of intuition is usually associated with the a priori forms of space and time. In my paper, firstly, I want to demonstrate that intuition is very complex and has different functions for transcendental consciousness and plays an important role in each function, secondly, to substantiate the thesis that this concept is key to understanding the principle of Kant's transcendental philosophy, and thirdly, to point out some aporias or problems associated with this concept. Here are some difficulties: the relationship between pure intuition and empirical intuition is problematic, and the function of intuition and representation is difficult to distinguish unambiguously.  In my article, I will consider several key points in Kant's philosophy for which the concept of intuition plays its own special function.